POLITICAL STUDY OF LAW LAW NUMBER 8 OF 1981 CONCERNING THE CRIMINAL PROCEDURE CODE IN TERMS OF PRETRIAL LEGAL ASPECTS - Lewiaro Laia (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
The development of the authority of pretrial institutions in Indonesia begins with increasing the pretrial authority to the authority of investigators to be able to re-establish legal subjects (persons and / or legal entities) as suspects with the same evidence. The state organ that plays a dominant role in determining changes to the authority of pretrial institutions in Indonesia is the Constitutional Court (MK) which in terms of the aspect of state organ power is in the judicial branch of power (not executive or even legislative). It's just that the legal products stipulated by the Constitutional Court are more in the nature of forming laws and regulations which are the authority of the legislative and executive state organs. Since its inception, the Constitutional Court has been designed to oversee the constitution in the sense of keeping the law consistent, in line, and not contrary to the Constitution. In this case, there is a kind of constitutionalism barrier that strictly limits the Constitutional Court as a constitutional judiciary not to interfere in the realm of legislative power. Therefore, as a judicial institution, the Constitutional Court in principle should only state that articles/paragraphs/parts or all laws are contrary or not contrary to the constitution. In such duties and authorities, the Constitutional Court should not be allowed to make decisions of a regulatory nature, should not cancel laws or the contents of laws that the Constitution declares open (handed over arrangements to the legislature), and should not also make decisions that are ultra petita (let alone those that are positive legislature).